Investigation of endohelmintes in snail (Helix lucorum, Linneaus, 1758) living in Keban Region of Elazig - Saglam, Naim; Gokhan, H. Bayram (Ege Univ, 2006)
In this study, total 20 snails (Helix lucorum) obtained from Keban Region of Elazig were examined interm of endohelmintes. At the end of parasitological examination of snails, Paragonimus sp. (Trematoda; Digenea) and Protostrogylus sp. (Nematoda; Metastrongyloidea) were determined in the intestine of snails. The abundance, prevalance and mean intensity for Paragonimus sp. were found 20%, 5% and 4 parasites per snail respectively. These values for Protostrongylus sp. were also found 30%, 5% and 6 parasites per snail respectively. It was determined that both parasites were not mature form, they use snail as a host.
Keywords: Snail; Helix lucorum; Endohelmint; Paragonimus sp.; Protostrogylus sp